Very low food security in the USA is linked with exposure to violence. Issue 1 (22nd February 2013) - Chilton, Mariana M; Rabinowich, Jenny R; Woolf, Nicholas H
Abstract: Objective: To investigate characteristics of exposure to violence in relation to food security status among female-headed households. Design: Ongoing mixed-method participatory action study. Questions addressed food insecurity, public assistance, and maternal and child health. Grounded theory analysis of qualitative themes related to violence was performed. These themes were then categorized by food security status. Setting: Homes of low-income families in Philadelphia, PA, USA. Subjects: Forty-four mothers of children under 3 years of age participating in public assistance programmes. Results: Forty women described exposure to violence ranging from fear of violence to personal experiences with rape. Exposure to violence affected mental health, ability to continue school and obtain work with living wages, and subsequently the ability to afford food. Exposure to violence during childhood and being a perpetrator of violence were both linked to very low food security status and depressive symptoms. Ten of seventeen (59 %) participants reporting very low food security described life-changing violence, compared with three of fifteen (20 %) participants reporting low food security and four of twelve (33 %) reporting food security. Examples of violent experiences among the very low food secure group included exposure to child abuse, neglect and rape that suggest exposure to violence is an important factor in the experience of very low food security. Conclusions: Descriptions of childhood trauma and life-changing violence are linked with severe food security. Policy makers and clinicians should incorporate violence prevention efforts when addressing hunger.